The burden of alcoholism in fifteen years of liver cirrhosis hospital admissions in portugal - Marinho, R. T.; Duarte, H.; Giria, J.; Nunes, J.; Ferreira, A.; Velosa, J. (Liver International, 2015)
Background and Aims: Deploying a longitudinal perspective, we observe how cirrhosis caused mortality rates in Portugal are converging with the levels reported in the European Union (15 countries). However, we still lack analysis of the burden of alcoholic cirrhosis in terms of hospital admissions and associated mortality. As Portugal may be considered a paradigmatic case in Europe, our aim was to characterize the evolution of hospital admissions for alcoholic cirrhosis between 1993 and 2008 and draw conclusions for other countries. Methods: Retrospective analysis of the hepatic cirrhosis admissions in 97 Portuguese state hospitals was carried out based on the National Registry. Results: We report a convergence in terms of mortality rates resulting from cirrhosis between Portugal and European Union (a differential of 6.7 deaths per 100 000 habitants in 1994 to 0.4 in 2008). We accounted for 81 543 hospital admissions for cirrhosis: 84% for alcoholic cirrhosis and 16% for non-alcoholic cirrhosis. Hospital admissions have increased 29% in men and with no increase in women. In the male, alcoholic cirrhosis patient group aged between 40 and 54, the rise in hospital admissions was more pronounced with an increase of around 45%. These patients underwent longer lengths of stay and reported higher mortality rates and passing away 20 years earlier than the average national expectancy of life. Conclusions: These data draw attention to the burden of alcohol consumption not only in Portugal but also in other countries and its impacts on hospital systems and on policy making.